2012
DOI: 10.1177/1536504212446466
|View full text |Cite
|
Sign up to set email alerts
|

Mounting Opposition to Vivisection

Abstract: Justin R. Goodman, Casey A. Borch, and Elizabeth Cherry discuss public attitudes toward animal testing and its growing opposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In addition, most (76%) agreed that “there needs to be more research into alternatives to animal experimentation” [ 30 ]. In the United States in 2011 the Gallup’s Values and Beliefs survey found that when asked whether medical testing on animals is morally acceptable or morally wrong, 43% (including 54% of those age 18-29 yr) responded ‘morally wrong’ [ 31 ]. Two recent surveys did ask for some elaboration on reasons for supporting AR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most (76%) agreed that “there needs to be more research into alternatives to animal experimentation” [ 30 ]. In the United States in 2011 the Gallup’s Values and Beliefs survey found that when asked whether medical testing on animals is morally acceptable or morally wrong, 43% (including 54% of those age 18-29 yr) responded ‘morally wrong’ [ 31 ]. Two recent surveys did ask for some elaboration on reasons for supporting AR.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Gallup Organization cross-sectional survey of approximately 1,000 Americans, opposition to animal testing increased from 33 to 43 percent between 2001 and 2011. 16 There are also growing concerns about the possibility of validly translating animal research fi ndings to the human conditions they are intended to model. There are acknowledged inadequacies in the predictive value and evidential weight of animal experimentation, 17 and systematic reviews and meta-analyses have demonstrated that fi ndings in animals are not necessarily reliable indicators of the promise and safety of human clinical research.…”
Section: Reasons For the Urgent Need For A Beecher-style Examination mentioning
confidence: 99%
“…In addition, to some extent, animal protection organizations have promoted the public's opposition to the use of animals in the experiments from 8% in 1948 to 50% in 2015. Also, the phenomenon of opposition to animal experiments is widespread in Europe and India and has garnered wide attention (Goodman et al, 2012;Roten, 2009;Singh, 2012). According to an American public opinion survey, people who believe that animal testing has an impact on scientific breakthroughs still hope that animals used in these ways can be treated humanely (Frasch, 2016).…”
Section: Introductionmentioning
confidence: 99%